(untitled) (Research, Society and Development, 2022)
The process of creating micro and small companies (MPEs) is directly related to entrepreneurship and it has grown a lot in Brazil in recent years. In addition, MPEs currently play an important role in the economy, as they are identified as sources of employment and income. In this context, the effectuation and causation logic defined by Sarasvathy (2001), are explored in this article in order to understand the process of creating these companies, which when they start from the causal principles focus on the selection of the means to achieve a predetermined objective and when they start from the effectual principles, select the set of means and focus on the possible effects that can be created from them. Thus, the objective of this study is to analyze the process of creating companies based on the causation and effectuation approaches. To achieve this goal, a qualitative research was carried out, through a semi-structured interview with five entrepreneurs of micro and small companies in the municipality of Salgueiro, in Pernambuco. Data analysis was carried out using the content analysis technique, which made it possible to identify causal and actual elements in the speech of each interviewee, which were coded using the atlas.ti software. As a result of the research it was possible to verify that the creation processes of these companies are marked mainly by effectual elements. Therefore, it is concluded that the effectuation logic is more present in the creation process of these five companies, mainly with regard to the question of contingency exploration, the strongest principle of the theory in all the interviewees.